Evaluasi Kepentingan Dan Kepuasan Masyarakat Terhadap Layanan Free Trade Agreement Center di Indonesia - Darmawan, Diana (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2022)
Indonesia already has several trade agreements with its partner countries, but their utilization is still not optimal. One of the causes is asymmetric information between the government and private sector firms, where the information obtained by these firms is not received perfectly. To that end, the Ministry of Trade established a Free Trade Agreement (FTA) Center to assist the government in overcoming asymmetric information and optimizing the use of trade agreements. To that end, the Ministry of Trade established the Free Trade Agreement Center or FTA Center to assist the government in overcoming asymmetric information and optimizing the utilization of trade agreements. This study measures the suitability of the implementation of the tasks and targets of the FTA Center in five regions by evaluating the interests and satisfaction of the firms towards the FTA Center's services by distributing questionnaires and interviews as data collection techniques. Based on the respondent's data, the results show that in the aggregate the results of the study show that various aspects of satisfaction and interest are already at a high satisfaction and importance index, namely openness/easy access to information, attitudes of experts, abilities and skills of experts, access to services, service effectiveness and efficiency, as well as complaint handling. However, the FTA Center can improve the quality in the aspects of service information, facilities/infrastructure, and service completion time